Relações sociais, conflitos e espaços de sociabilidade: formas de convívio no Município de Vitória, 1850-1872 - Bastos, Fabíola Martins (2009)
The dissertation discuss the ways of established sociability’s through the population of Vitória County, between the year 1850 and 1872. The initial date was choose by the alterations that occurred on Espírito Santo territory in 1850 with the expansion of the coffee’s fieldwork, when the north fluminense’s culture spreaded, reaching out the capixaba’s soil. The final mark it’s locate in the year of 1872, when strong changes came from “Ventre Livre Law”, with the arise of legal associations and abolisher’s clubs, that reflects the ways of living in the beginning of 1870 decade. The first years of that decade marked the transition of the informal to a formal sociability, characteristic by lay and societies’ associations, communities. The meetings meant to entertain and the day by day talk, slowly, lost space to the meeting in privates establishments with the same purpose. In this dissertation, therefore, it developed the concept of sociability, based upon the formulations of Max Weber, Arlette Farge, Maurice Agulhon and Maria Alexandre Lousada. The socials’ relations built daily are discussed in the streets, waterfronts, parks, stores, quay piers and roads. The sources of this dissertation consist on “Correio da Victoria” and “Jornal da Victoria” and criminal’s process of insult and physical aggression. The informal way of daily built and rightful by the “capixaba” population’s is clear sought in this documents. Equally sought to determined the limits of this daily living informally created that resulted in sociabilities’ violence.